Coverage-level and predictors of maternity continuum of care in Nigeria: implications for maternal, newborn and child health programming (2023)
Background Completing maternity continuum of care from pregnancy to postpartum is a core strategy to reduce the burden of maternal and neonatal mortality dominant in sub-Saharan Africa, particularly Nigeria. Thus, we evaluated the level of completion, dropout and predictors of women uptake of optimal antenatal care (ANC) in pregnancy, continuation to use of skilled birth attendants (SBA) at childbirth and postnatal care (PNC) utilization at postpartum in Nigeria. Methods A cross-sectional analysis of nationally representative 21,447 pregnancies that resulted to births within five years preceding the 2018 Nigerian Demographic Health Survey. Maternity continuum of care model pathway based on WHO recommendation was the outcome measure while explanatory variables were classified as; socio-demographic, maternal and birth characteristics, pregnancy care quality, economic and autonomous factors. Descriptive statistics describes the factors, backward stepwise regression initially assessed association (p<0.10), multivariable binary logistic regression and complementary-log–log model quantifies association at a 95% confidence interval (α=0.05). Results Coverage decrease from 75.1% (turn-up at ANC) to 56.7% (optimal ANC) and to 37.4% (optimal ANC and SBA) while only 6.5% completed the essential continuum of care. Dropout in the model pathway however increase from 17.5% at ANC to 20.2% at SBA and 30.9% at PNC. Continuation and completion of maternity care are positively drive by women; with at least primary education (AOR=1.27, 95%CI=1.01–1.62), average wealth index (AOR=1.83, 95%CI=1.48 –2.25), southern geopolitical zone (AOR=1.61, 95%CI=1.29–2.01), making health decision alone (AOR=1.39, 95%CI=1.16–1.66), having nurse as ANC provider (AOR=3.53, 95%CI=2.01–6.17) and taking at least two dose of tetanus toxoid vaccine (AOR=1.25, 95%CI=1.06–1.62) while women in rural residence (AOR=0.78, 95%CI=0.68–0.90) and initiation of ANC as late as third trimester (AOR=0.44, 95%CI=0.34–0.58) negatively influenced continuation and completion. Conclusions 6.5% coverage in maternity continuum of care completion is very low and far below the WHO recommended level in Nigeria. Women dropout more at postnatal care than at skilled delivery and antenatal. Education, wealth, women health decision power and tetanus toxoid vaccination drives continuation and completion of maternity care. Strategies optimizing these factors in maternity packages will be supreme to strengthen maternal, newborn and child health.